2017
DOI: 10.1017/s1368980017002701
|View full text |Cite
|
Sign up to set email alerts
|

Battle of plates: a pilot study of an approach–avoidance training for overweight children and adolescents

Abstract: Automatic tendencies in children can be trained, too. The implementation of AAT in the treatment of obesity might support the modification of an unhealthy nutrition behaviour pattern. Further data from randomized controlled clinical trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 40 publications
(83 reference statements)
3
6
0
Order By: Relevance
“…In the current study, although between-condition changes were not significant, analyses per condition showed that our 10 sessions of AAT resulted in a significant reduction in approach tendencies toward unhealthy and healthy food pictures. This finding is in line with previous research showing that during a six-session AAT, obese children successfully learned to reduce their automatic approach tendencies toward snack food pictures, but otherwise the study of Warschburger and colleagues (2017) showed an increase in approach tendencies toward vegetable items. Further, the current training resulted also in a significant reduction in craving but failed to reduce the attentional bias toward unhealthy food pictures.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, although between-condition changes were not significant, analyses per condition showed that our 10 sessions of AAT resulted in a significant reduction in approach tendencies toward unhealthy and healthy food pictures. This finding is in line with previous research showing that during a six-session AAT, obese children successfully learned to reduce their automatic approach tendencies toward snack food pictures, but otherwise the study of Warschburger and colleagues (2017) showed an increase in approach tendencies toward vegetable items. Further, the current training resulted also in a significant reduction in craving but failed to reduce the attentional bias toward unhealthy food pictures.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that children with overweight and obesity versus those with normal weight did not show greater approach behavior towards high-calorie foods during the AAT is contrary to expectations, but fits into the inconsistent findings of previous studies in child and adult samples (e.g., References [80,81]). Within an intervention study in 276 8–16 years old youth, baseline AAT data already indicated avoidance tendencies for snack foods in children with obesity, much like in the present study; however, there were no data of a normal-weight control group available [82]. Similarly, the only study investigating adults with obesity did not find an approach bias towards high- or low-calorie foods [81], while university students with high levels of food cravings showed greater approach behavior towards food cues than adults with low levels of food craving [83].…”
Section: Discussionsupporting
confidence: 51%
“…With respect to the question of general trainability, our findings support data from a small pilot study (Warschburger et al, ) and suggest that AAT is also suitable for children and adolescents with obesity. In line with other studies using single sessions (Dickson et al, ; Fishbach & Shah, ; Maas et al, ; Schumacher et al, ), we observed a modification of the AAB after the last training session.…”
Section: Discussionsupporting
confidence: 86%
“…Hence, future studies should directly compare single-and multiple-session training. Multiple sessions of a highly standardized training intervention with a repetitive design might also be too boring for children (Warschburger et al, 2017). A gamification of computer-based applications for children might be more appealing (Boendermaker, Prins, & Wiers, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation